Dead academics: what can we learn about academic work and life from obituaries?. (1st July 2008) - Tight, Malcolm
Abstract : This article analyses the obituaries of 100 academics published in the British quality press in 2007 to see what they tell us about the changing nature of contemporary academic work, and how it is presented in this particular genre of writing. It concludes that the influence of Oxbridge and the American higher education system, and the dominance of men, remain strong in the senior levels of academic life that make it into the obituary pages. The obituaries also illustrate the impact of global events and trends, such as world war and the international mobility of highly skilled labour, on academe. At an individual level, they present a picture of almost mythic achievement, brought down to earth by accounts of caring and essential eccentricity.